NATURALISASI PEMAIN TIMNAS SEPAKBOLA INDONESIA DAN PERMASALAHANNYA DALAM HUKUM KEIMIGRASIAN: Naturalization of Indonesian National Football Team Players and Its Issues in Immigration Law - Firyaldha Jelondra; Tri Sulistyowati (Faculty of Law, Universitas Trisakti, 2025)
The naturalization of foreign football players for the Indonesian national team presents legal challenges, particularly concerning the relationship between citizenship and immigration regulations. Players must fulfill administrative requirements such as limited stay visas (VITAS), limited stay permits (KITAS), and passports. The research questions in this study are, What are the legal issues in the naturalization process of Indonesian national football team players and How does immigration law analyze the required documents and the passport issuance procedures for naturalized players? This research applies a normative legal method with a statutory and case study approach. The findings show that the absence of a written guideline on the selective policy principle and weak inter-agency coordination hinder the efficiency of the naturalization process. Administrative issues involving ITAS, ITAP, and police clearance (SKCK), as well as biometric verification procedures, often delay passport issuance. Therefore, harmonization between Law No. 12 of 2006 on Citizenship and Law No. 6 of 2011 on Immigration is essential to ensure that the naturalization process is legally valid, efficient, and supports the players’ official participation in the national team.